2022
DOI: 10.1108/ijebr-02-2022-0164
|View full text |Cite
|
Sign up to set email alerts
|

Stay alert, save businesses. Planning for adversity among immigrant entrepreneurs

Abstract: PurposeAgainst the theoretical backdrop of the embeddedness and the resilience literatures, this paper investigates if and how SMEs' planning for adversity affects firms' performance.Design/methodology/approachThe paper develops hypotheses that investigate the link between the risk management of immigrant-led and native-led SMEs and their performance and draw on novel data from a survey on 900 immigrant- and 2,416 native-led SMEs in 5 European cities to test them.FindingsImmigrant-led SMEs are less likely to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Weitzen (1989) believes that is the best strategy for high-risk situations and execution. Previous research (Campagnolo, 2022; Welter, 2021) found that even when there is no crisis, businesses must plan for adversity in order to grow and perform better.…”
Section: Resultsmentioning
confidence: 99%
“…Weitzen (1989) believes that is the best strategy for high-risk situations and execution. Previous research (Campagnolo, 2022; Welter, 2021) found that even when there is no crisis, businesses must plan for adversity in order to grow and perform better.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that what makes the strategy work is organizational abilities to sufficiently prepare to use this strategy and effectively reuse it at times of other adverse events (Battisti et al, 2019;Corvello et al, 2022). Scholars are thus particularly interested in how both large and smaller organizations prepare for adverse events through crafting response strategies that fit their organizations (Campagnolo et al, 2022) and, particularly, whether and how organizational size and age play a role in strategy development, its adaptation in response to unfolding adversities and its further re-adaptation in times of forthcoming adversities of a similar nature, impact and timespan (Herbane, 2019). Even though smaller organizations are relatively more flexible and, on average, have a higher speed of decision making due to their rather simple organizational structure (Morgan et al, 2020), large organizations have a notable advantage when it comes to both crafting success strategies and further using/ reusing them when adversities strike (Baker and Nelson, 2005;Langevang and Namatovu, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2022). Scholars are thus particularly interested in how both large and smaller organizations prepare for adverse events through crafting response strategies that fit their organizations (Campagnolo et al. , 2022) and, particularly, whether and how organizational size and age play a role in strategy development, its adaptation in response to unfolding adversities and its further re-adaptation in times of forthcoming adversities of a similar nature, impact and timespan (Herbane, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%